A vertiginosa vida da linguagem : literatura e biopolítica em Caio Fernando Abreu - João Lúcio Xavier (2016)
The present study intent to propose a reading of some short stories from Caio Fernando Abreu (1948-1996) opus, aiming to establish a dialogue between some of his texts and the contemporary discussion about biopolitics. By showing multiple times characters in misfit or displacement considering the standard demanded by the social rules, Caios characters suffer prejudice and oppression from the environment they live in. If such oppression can be related to the bio politics discussion, according to which the modern societies live by the biopower yoke that tries by all the possible means and the most sophisticate ways to control the individuals life in every respects possible, it is also necessary to think about the authors own production seems to aim to resistance potential against this power. In a motion of dual writing, the authors seems to point, at the same time, to domination ways and to the possible resistance potential that emanate from the own individuals life (biopotencial) of those who see themselves as excludes or controlled. By showing these means of possible counter power, Caios literature seems to propose that even from the greatest ways of control it is always possible to resist.